2014
DOI: 10.1037/a0036501
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety symptoms and drinking behaviors among college students: The mediating effects of drinking motives.

Abstract: The impact of social anxiety on negative alcohol-related behaviors among college students has been studied extensively. Drinking motives are considered the most proximal indicator of college student drinking behavior. The current study examined the mediating role of drinking motives in the relationship that social anxiety symptoms have with problematic (alcohol consumption, harmful drinking, and negative consequences) and safe (protective behavioral strategies) drinking behaviors. Participants were 532 undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…The etiology of co‐occurring social anxiety and substance use problems is commonly attributed to coping‐motivated substance use as an underlying mechanism (Buckner et al., ). Yet, prior investigations of alcohol or marijuana use have found that students with social anxiety experience more substance‐related problems based on both positively reinforcing (e.g., enhancement; Villarosa et al., ) and negatively reinforcing motives (e.g., conformity; Buckner et al., ,b). These inconsistencies may be due to the lack of attention to students who use both alcohol and marijuana (i.e., concurrent users).…”
mentioning
confidence: 96%
“…The etiology of co‐occurring social anxiety and substance use problems is commonly attributed to coping‐motivated substance use as an underlying mechanism (Buckner et al., ). Yet, prior investigations of alcohol or marijuana use have found that students with social anxiety experience more substance‐related problems based on both positively reinforcing (e.g., enhancement; Villarosa et al., ) and negatively reinforcing motives (e.g., conformity; Buckner et al., ,b). These inconsistencies may be due to the lack of attention to students who use both alcohol and marijuana (i.e., concurrent users).…”
mentioning
confidence: 96%
“…Conformity and coping motives are less frequently reported, but are consistently and more strongly associated with alcohol problems compared to social and enhancement motives (Kuntsche et al, 2005). Motives mediate the effect of alcohol expectancies on use (Williams & Clark, 1998), the effect of social anxiety on negative alcohol consequences (Villarosa, Madson, Zeigler-Hill, Noble, & Morn, 2014), and the effect of bullying on drinking (Archimi & Kuntsche, 2014). Further, motives moderate the effect of ambivalence on drinking (Foster, et al, 2014) and the effect of posttraumatic stress disorder on drinking (Simpson, Stappenbeck, Luterek, Lehavot, & Kaysen, 2014).…”
mentioning
confidence: 99%
“…Indeed, approximately 80% of all AUD cases occur prior to 40 years of age (Eaton et al, 2012). Alcohol use among socially anxious individuals is usually much harder to control than in individuals reporting fewer social anxiety symptoms, and early drinking in order to cope is known to predict later alcohol misuse in adulthood (Blumenthal et al, 2010; Patrick et al, 2011; Villarosa et al, 2014). …”
Section: Current Implications Of Alcohol Use Amongst Socially Anximentioning
confidence: 99%